Postural Evaluation of Patients Subjected to Modified Radical Mastectomy by Means of Computer Photogrammetry - Melo, Marcela Silvino Iglésias (2011)
Introduction: Modified radical mastectomy surgery can result in changes in posture of women stricken with breast cancer. In order to more precisely develop a physiotherapeutic regimen, computer photogrammetry is being widely used as a diagnostic tool, especially for postural evaluation. Objective: The aim of this study was to analyze the posture of patients who have undergone modified radical mastectomy by means of computer photogrammetry. Methods: This is a cross-sectional study, conducted at the Physiotherapy Center of the Cancer Hospital of Pernambuco, from March to May 2007. The sample consisted of 22 women who had undergone modified radical mastectomy for treatment of breast cancer, with ages from 37 to 60 years, who had not undergone postural physiotherapeutic evaluation in the pre-surgery phase. The images were captured in four protocols of postural analysis which were accomplished in the anterior and posterior views, as well as in the left and right lateral views. Subsequently, the images were analyzed using the software SAPO, version 0.67. In the comparative analyses, the Student’s-t test was used, with significance level of p<0.05 used for all the variables and performed with the SPSS program, version 8.0. Results: Several postural changes were observed, but the main changes related to surgical intervention were the forward disposition of the head (25.84±11.33, p=0.001) and protrusion of shoulder abduction (29.79±7.64, p=0.001). Conclusion: Women who undergo surgical treatments such as modified radical mastectomy for treatment of breast cancer can develop postural changes and the most common ones related to the surgery are forward disposition of the head and protrusion of the shoulder abduction.